Mitochondrial barcodes of dragonflies and damselflies originated from Taman Negara Endau Rompin, Johor, Malaysia - Y. T., Lam; K. R., Kamarudin; M. Z., Zakaria; M. S. S., Omar; L., Tokiman; P. N. S., Jahari; F., Mohd Salleh (IOP Publishing, 2021)
Dragonflies and damselflies (Odonates) are important biological indicators in freshwater ecosystems. However, identification among Odonates is often challenging due to their similar morphological features. Therefore, the incorporation of morphological identification by taxonomists and validation using mitochondrial barcodes such as cytochrome c oxidase subunit I (COI) can be a more reliable approach to enhance the accuracy in species identification. In this study, four COI barcodes for Malaysian dragonflies (Neurothemis fluctuans) and damselflies (Neurobasis chinensis, Aristocypha fenestrella and Sundacypha petiolata) were generated. Three of the generated barcodes (D2 COI, D4 COI and D5 COI) supported the species identified by taxonomists meanwhile D3 COI deduced that the damselfly species was misidentified due to the very similar morphology between the same genus of damselfly. All of the COI barcodes are now available in the GenBank with the accession numbers of MT266926.1 (D2 COI), MT266925.1 (D3 COI), MT269676.1 (D4 COI) and MT266924.1 (D5 COI).